Smoking, age, nodal disease, T stage, p16 status, and risk of distant metastases in patients with squamous cell cancer of the oropharynx. Issue 5 (11th December 2018) - Beitler, Jonathan J.; Switchenko, Jeffrey M.; Dignam, James J.; McDonald, Mark W.; Saba, Nabil F.; Shin, Dong M.; Magliocca, Kelly R.; Cassidy, Richard J.; El‐Deiry, Mark W.; Patel, Mihir R.; Steuer, Conor E.; Xiao, Canhua; et al.
Abstract : Background: With an expectation of excellent locoregional control, ongoing efforts to de‐intensify therapy for patients with human papillomavirus–associated squamous cell oropharyngeal cancer necessitate a better understanding of the metastatic risk for patients with this disease. The objective of this study was to determine what factors affect the risk of metastases in patients with squamous cell cancers of the oropharynx. Methods: Under a shared use agreement, 547 patients from Radiation Therapy Oncology Group 0129 and 0522 with nonmetastatic oropharyngeal squamous cell cancers who had a known p16 status and smoking status were analyzed to assess the association of clinical features with the development of distant metastases. The analyzed factors included the p16 status, sex, T stage, N stage, age, and smoking history. Results: A multivariate analysis of 547 patients with a median follow‐up of 4.8 years revealed that an age ≥ 50 years (hazard ratio [HR], 3.28; P = .003), smoking for more than 0 pack‐years (HR, 3.09; P < .001), N3 disease (HR, 2.64; P < .001), T4 disease (HR, 1.63; P = .030), and a negative p16 status (HR, 1.60; P = .044) were all factors associated with an increased risk of distant disease. Conclusions: Age, smoking, N3 disease, T4 disease, and a negative p16 status were associated with the development of distant metastases in patients with squamous cell cancers of the oropharynx treated definitively with concurrent chemoradiation. Abstract : According to an analysis of more than 500 patients with squamous cell cancer of the oropharynx, smoking for more than 0 pack‐years ( P < .001), N3 disease (AJCC 7th edition) ( P < .001), an age ≥ 50 years ( P = .003), T4 disease (AJCC 7th edition) ( P = .030), and a negative p16 status ( P = .044) are associated with an increased risk of distant disease. Increased age and p16 status are newly identified risk factors for the development of metastases in patients with squamous cell cancers of the oropharynx.